2020
DOI: 10.4111/icu.2020.61.2.216
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of patient-derived three-dimensional organoid culture in renal cell carcinoma

Abstract: Renal cell carcinoma is a heterogeneous kidney cancer, and over 403,000 cases were reported worldwide in 2018. Current methods for studying renal cell carcinoma are limited to two-dimensional (2D) culture of primary cell lines and patient-derived xenograft models. Numerous studies have suggested that 2D culture poorly represents the diversity, heterogeneity, and drugresistance of primary tumors. The time and cost associated with patient-derived xenograft models poses a realistic barrier to their clinical utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Na et al established a concrete protocol of PDO culture directly from surgical resected ccRCC sample. Such PDO preserves the morphology and biomarker expression of parental tumors ( 22 ). Grassi et al also reported an approach to establishing and passaging normal kidney organoids and RCC PDO from surgically resected tissues.…”
Section: Evolution Of Patient-derived Organoid Model In Renal Cell Ca...mentioning
confidence: 99%
“…Na et al established a concrete protocol of PDO culture directly from surgical resected ccRCC sample. Such PDO preserves the morphology and biomarker expression of parental tumors ( 22 ). Grassi et al also reported an approach to establishing and passaging normal kidney organoids and RCC PDO from surgically resected tissues.…”
Section: Evolution Of Patient-derived Organoid Model In Renal Cell Ca...mentioning
confidence: 99%
“…Crucially, the expression of characteristic biomarkers was more likely to be retained in PDOs than two-dimensional culture models [ 54 ]. For example, the response of colon cancer organoids to the inhibition of the histone methyltransferase EZH2 was correlated to expression of the pro-apoptotic BIK gene [ 55 ].…”
Section: Cancer Biomarkersmentioning
confidence: 99%
“…The lacks of conventional cancer models are microenvironment, stromal compartments, organspecific function, immune system, genetic heterogeneity (2,13,14). The promising organoid technology bridges the gap between traditional in vitro and in vivo cancer models (15). Tumoroids have been generated from tissue biopsies, surgical resections, ascitic fluid, and circulating tumor cells (16)(17)(18)(19).…”
Section: Organoid Modeling For Cancermentioning
confidence: 99%